Effect of Eyelid Involvement in the Reconstruction of Medial Canthal Defects - Altin Ekin, Meryem; Karadeniz Ugurlu, Seyda (Facial Plastic Surgery, 2019)
The purpose of this study was to present surgical techniques for the reconstruction of medial canthal defects with and without the involvement of the eyelid. This study included 31 patients who underwent medial canthal reconstruction after tumor excision during a 6-year period. Data regarding patient demographics, defect size, tumor pathology, surgery techniques, functional and cosmetic outcomes, and complications were recorded. The reconstructive methods used in the study were divided into groups as per the site of the defect (medial canthal, medial canthal with upper eyelid, medial canthal with lower eyelid, and medial canthal with both eyelids). The most common histopathological diagnosis of the lesions was basal cell carcinoma (74.2%). Postoperative complications (6.4%) included flap necrosis in one patient and lid margin notching in another. Among patients who underwent reconstruction, 8 (25.8%) had only medial canthal defect, 6 (19.3%) had medial canthal defect extending to the upper eyelid, 7 (22.6%) had medial canthal defect extending to the lower eyelid, and 10 (32.3%) had medial canthal defect extending to both the eyelids. The functional outcome was regarded as normal in 30 (96.8%) patients and limited in 1 (3.2%) patient. Cosmetic outcomes were satisfactory in all the patients. The use of alternative reconstructive approaches for different subunits of the medial canthus is an efficient method to achieve superior functional and cosmetic outcomes.
Keywords: basal cell carcinoma; eyelid; medial canthal defect; reconstruction; tumor